Innate Immunity Toll‐Like Triad TLR6‐1‐10 and Its Diversity in Distinct Horse Breeds - Karla Stejskalova; Leona Vychodilova; Eva Janova; Jan Oppelt; Petr Horin (Veterinary Medicine and Science)
ABSTRACT Toll‐like receptors (TLRs) play important roles in innate immunity and developmental processes. Due to their nature as molecular pattern recognition receptors, their genetic diversity may reflect the effects of various pathogen pressures. Here, the extent of variability in the TLR1‐6‐10 gene cluster in three geographically and historically distinct breeds of horses was analysed. A genetically diverse group of representatives of 14 other horse breeds provided additional information on the variability of this gene cluster in the domestic horse. Altogether, 25 SNPs were identified in the TLR6‐1‐10 gene cluster across the 4 equine breed groups studied, of which 7 were synonymous and 18 non‐synonymous. Twenty‐eight inferred SNPs and 22 in silico translated amino acid haplotypes were identified. A predominant major haplotype present in all breed groups along with several group‐specific haplotypes were identified. Strong linkage disequilibrium was detected for several SNPs, as well as effects of pervasive, site‐specific selection. The existence of a major haplotype suggests it may confer a selective advantage across breeds. Less frequent breed‐specific haplotypes may represent variability required or beneficial for responses to local pathogen pressures. Purifying site‐specific selection was detected in the TIR domain and its vicinity in TLR6, whereas AA sites under diversifying selection were located in LRR domains and/or their surroundings in TLR1. Population structure models based on immune‐related TLR6‐1‐10 markers did not distinguish between breed groups, whereas in models based on neutral microsatellite markers, breed groups clustered separately. This supports the assumption that the diversity of the TLR6‐1‐10 cluster is of adaptive value. The TLR6‐1‐10 alleles and haplotypes identified represent potential candidate markers for disease association studies.